Tutela antecipada na defesa dos direitos da personalidade e a responsabilidade dos meios de comunicação - Bragatte, Sergio (2005)
This work aimed at bringing together two seminal aspects regarding the defense of personal rights (i) the responsability of the mass media and (ii) the adoption of speedy judicial action when illegal behaivor by the media has been verified.